Oppian's Halieutica - Kneebone, Emily (Cambridge University Press, 2020)
Oppian's Halieutica is a dazzling five-book Greek didactic poem about the sea and its wily, chaotic inhabitants. This book offers the first sustained reading of the poem as a didactic epic that meditates on the place of human beings within the cosmos at large, and on the lessons we can learn from fish. Using a combination of close reading and wider interpretative lenses, this book examines the literary texture and cultural relevance of the Halieutica by analysing its sophisticated refraction of earlier literary-critical theories and hexameter traditions, its commentary on human-animal relations, and its contribution to imperial Greek literary, political, and cultural debates. The book demonstrates the importance and cultural centrality of this understudied Greek didactic epic; it is written for students and scholars of imperial Greek literature and culture (including the ancient novel), ancient heroic and didactic epics, and those interested in human-animal relations in the ancient world.
10.1017/9781108892728
Keywords: Oppian; Halieutica; Didactic poetry; Greek; Fishes in literature; Fishing in literature; Human-animal relationships in literature; Oppian; active 2nd century; Halieutica; Didactic poetry; Greek; History and criticism